PENENTUAN PRODUKTIVITAS DAERAH KABUPATEN TERBAIK SEBAGAI PENGHASIL TANAMAN SAYURAN CABAI DI PROVINSI SUMATERA SELATAN MENGGUNAKAN DIAGRAM KARTESIUS - Hendrixon Hatta; Nursanty Nursanty (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The production of chili plants in South Sumatra Province spread in seventeen regencies and cities. However, the Regency / City and South Sumatra Provincial Government do not know the productivity advantages for each region; therefore, further research needed to find out the best productive regencies/cities in producing chili vegetable crops. The method used in this research was a descriptive statistical analysis using regression analysis techniques and cartarsius diagrams. The research variables were the amount of production and productivity. The results show that Ogan Komering Ilir District was the best regency in terms of productivity, so it could use as a local reference for other districts and cities in South Sumatra Province in an attempt to increase the productivity of chili vegetables.